THE IMPLEMENTATION OF THE QIRA’AH METHOD IN ARABIC LANGUAGE LEARNING FOR STUDENTS OF MA MAMBAUL ULUM PAITON PROBOLINGGO - Hotimah, Isnol; Nabihah, Azmiyatun (Al-Fakkaar, 2025)
The purpose of this study is to explore the effectiveness of implementing the Qiro’ah method through Qiro’atul Khobar in Arabic language learning at MA Mambaul Ulum Sukodadi Paiton, Probolinggo. This research aims to assess the extent to which students can master reading skills for Arabic news texts accurately, including pronunciation, intonation, and comprehension of the text’s content. The main focus is to improve students' reading abilities, which have been observed as suboptimal, by utilizing varied reading texts tailored to their interests. This study seeks to identify teaching strategies that can engage students and make them more active in learning Arabic. Topics such as Education, Inspirational Figures, and Local Wisdom are used to maintain students' motivation and prevent boredom. Furthermore, the study provides recommendations for future development of teaching materials with more interactive approaches, such as incorporating digital media or learning applications. These innovations are expected to create a more engaging and relevant learning experience for students, while also enhancing their participation in the learning process.